The application of new concepts of the assessment of the thyroid state to pregnant women - Fitzgerald, Stephen P.; Bean, Nigel G.; Fitzgerald, Samuel P.; Falhammar, Henrik (Frontiers in Endocrinology, 2022)
Recently proposed concepts regarding the nature and assessment of the thyroid state have provided a model more consistent with empiric evidence. It now appears likely that there are no such entities as thyroid set points and individual euthyroidism. Rather than there being discrete thyroid states, peripheral organ parameters are associated with thyroid function in a continuous manner. Thyroid hormone levels, and in particular, levels of free thyroxine now appear to be superior to thyrotropin levels as indicators of the thyroid state. Complicating the assessment of the correlations of the thyroid state with pregnancy outcomes are the contribution of the placenta to maternal thyroid function, fetal thyroid development, the multiple potential pathways to any particular outcome, the likely presence of small critical periods of time, the differing genetics of fetal and maternal tissues, and the unreliability of thyroid hormone assays. Nevertheless there is no apparent reason for there to be a change in pregnancy to the basic principles of thyroid hormone action. The relationships between mild abnormalities of the thyroid state and pregnancy outcomes and the value of treating such mild abnormalities remain uncertain and controversial. The evidence suggests that the further investigation of these clinical questions might better be based on thyroid hormone, particularly free thyroxine, levels. In the investigation of borderline low thyroid states the categories of subclinical hypothyroidism and isolated hypothyroxinemia might both be abandoned with attention being directed to low free thyroxine levels regardless of the TSH levels. For these changes to occur there would ideally be improvements in the assays for free thyroxine in pregnancy. The evidence suggests that, just as in the non-pregnant situation, pregnancy guidelines based on thyrotropin levels may need revision.